Long-term prognostic value of the combined assessment of clinical and computed tomography findings in type: An acute aortic dissection. Issue 45 (6th November 2020) - Hirata, Kenichiro; Oda, Seitaro; Suzuki, Ryusuke; Sugahara, Takeshi
Abstract : Abstract: Type A acute aortic dissection (TAAAD) carries a high mortality rate in the absence of surgical treatment. This study sought to determine whether combining the assessment of clinical and computed tomography (CT) findings can be used to predict the long-term all-cause mortality rate of patients with TAAAD. Eighty-five consecutive patients with TAAAD who had undergone CT imaging and surgery were retrospectively reviewed. For the clinical and CT findings, univariate testing followed by multivariate logistic regression analysis was conducted to identify independent predictors of death. Then, the area under the receiver operating characteristic curve of the combined prediction model was calculated. The long-term mortality rate was 34.1% in our cohort (a median follow-up period of 60 months). Multivariate logistic regression analysis identified the following presenting variables as predictors of death: male sex (odds ratio [OR]: 6.67; 95% confidence interval [CI]: 1.67–25.0; P  = .007), kidney malperfusion (OR: 2.18; 95% CI: 1.16–4.1; P  = .02), and descending aorta size (OR: 1.12; 95% CI: 1.00–1.25; P  = .05). Receiver operating characteristic curve analysis revealed an area under the receiver operating characteristic curve of 0.84 when using the combined model for prediction of long-term all-cause mortality ( P  ⩽ .01). The combined assessment of clinical and CT findings can reasonably predict the long-term prognosis of TAAAD with surgery.